Implications of Legal Loophole concerning Liability over Delay in Restitution Payment by Criminal Offender - Nurini Aprilianda; Ryan Ilham Fibriansyah (Jurnal Media Hukum, 2021)
Crime is harmful to society, especially to the victims. Legal protection should be taken into account to help the victims recover from the loss suffered. The protection can be made through the payment of restitution by either the offender or the third party. Such an issue has been addressed in the existing law, especially the Witness and Victim Protection Act 2014 (Amendment) and the Government Regulation No. 7 of 2018 concerning Compensation, Restitution, and Aid for Witness and Victim. Unfortunately, they do not impose any sanction over the delay in restitution payment by the third party or the offender. This paper aims at discussing the implication of this legal loophole. This normative legal research employs a statutory approach. It is found that the legal loophole has exposed the victims to secondary victimization due to uncertainty and injustice.